2006
DOI: 10.1385/bter:110:1:79
|View full text |Cite
|
Sign up to set email alerts
|

Contents of Metals in Some Wild Mushrooms: Its Impact in Human Health

Abstract: The concentrations of 7 metals (lead, cadmium, manganese, copper, nickel, silver, and chromium) were determined in 32 different species of wild mushrooms. The mushroom samples, which have been using for food and some medical purposes, were collected from Konya, an Inner Anatolian region of Turkey. The highest metal concentrations were determined as 39 mg/kg Pb and 3.72 mg/kg Cd in Trichaptum abietinum, 467 mg/kg Mn in Panaeolus sphinctrinus, 326 mg/kg Cu in Trametes versicolor, 69.4 mg/kg Ni in Helvella spadic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 38 publications
2
21
5
Order By: Relevance
“…The level of manganese content of P. eryngii var. ferulae which was obtained from various compost medium is lower compared to an earlier published report (Dogan et al 2006).…”
Section: Resultscontrasting
confidence: 72%
See 2 more Smart Citations
“…The level of manganese content of P. eryngii var. ferulae which was obtained from various compost medium is lower compared to an earlier published report (Dogan et al 2006).…”
Section: Resultscontrasting
confidence: 72%
“…Besides, the lowest copper level was found in natural wild sample ( Table 2). The reported copper values for P. eryngii was 16.5 mg kg -1 (Dogan et al 2006). Manganese contents of P. eryngii var.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Numerous studies have addressed the chemical composition of wild species, including recently reported values of PGEs and REEs [14][15][16][17][18][19][20][21][22]. Cultivated specimens have usually been analyzed with respect to the content of some elements in selected mushroom species only [23][24][25][26], in general, those important to trade.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated macroelements included potassium (18 500 mg kg −1 DM), calcium (4 200 mg kg −1 DM), magnesium (2 100 mg kg −1 DM) and sodium (285.0 mg kg −1 DM) [Ayaz et al 2011]. In turn, the contents of microelements were as follows: chromium (58.3 mg kg −1 DM), manganese (30.7 mg kg −1 DM), lead (24.5 mg kg −1 DM), copper (22.7 mg kg −1 DM), nickel (22.7 mg kg −1 DM), cadmium (0.68 mg kg −1 DM) and silver (0.26 mg kg −1 DM) [Doğan et al 2006]. Other studies confirmed the presence of aluminum (53.9 mg kg −1 DM), boron (16.4 mg kg −1 DM), cobalt (1.2 mg kg −1 DM) and tin (4.5 mg kg −1 DM) [Durkan et al 2011].…”
mentioning
confidence: 99%